The genesis of perinatal clinical psychology and its contemporary issues - Missonnier, Sylvain (Frontiers in Psychiatry, 2023)
The main aim of French clinical psychology is to explain the psychic processes of transformation, to which the subject is central. In this context, transformations in the perinatal period open an innovating field in perinatal clinical psychology focused on the conscious/subconscious, subjective/inter-subjective psychic reality of a subject who is in the process of becoming (or becoming once again) a parent and being born a human.